Insights in the maturational processes influencing hydrocortisone pharmacokinetics in congenital adrenal hyperplasia patients using a middle-out approach - Michelet, Robin; Bindellini, Davide; Melin, Johanna; Neumann, Uta; Blankenstein, Oliver; Huisinga, Wilhelm; Johnson, Trevor N.; Whitaker, Martin J.; Ross, Richard; Kloft, Charlotte (Frontiers in Pharmacology, 2023)
Hydrocortisone is the standard of care in cortisol replacement therapy for congenital adrenal hyperplasia patients. Challenges in mimicking cortisol circadian rhythm and dosing individualization can be overcome by the support of mathematical modelling. Previously, a nonlinear mixed-effects (NLME) model was developed based on clinical hydrocortisone pharmacokinetic pediatric and adult data. Additionally, a physiologically-based pharmacokinetic (PBPK) model was developed for adults and a pediatric model was obtained using maturation functions for relevant processes. In this work, a middle-out approach was applied. The aim was to investigate whether PBPK-derived maturation functions could provide a better description of hydrocortisone PK inter-individual variability when implemented in the NLME framework, with the goal of providing better individual predictions towards precision dosing at the patient level. Hydrocortisone PK data from 24 adrenal insufficiency pediatric patients and 30 adult healthy volunteers were used for NLME model development, while the PBPK model and maturation functions of clearance and cortisol binding globulin (CBG) were developed based on previous studies published in the literature. Clearance (CL) estimates from both approaches were similar for children older than 1 year (CL/F increasing from around 150 L/h to 500 L/h), while CBG concentrations differed across the whole age range (CBGNLME stable around 0.5 µM vs steady increase from 0.35 to 0.8 µM for CBGPBPK). PBPK-derived maturation functions were subsequently included in the NLME model. After inclusion of the maturation functions, none, a part of, or all parameters were re-estimated. However, the inclusion of CL- and/or CBG-maturation functions in the NLME model did not result in improved model performance for the CL maturation function (ΔOFV>-15.36) and the re-estimation of parameters using the CBG-maturation function most often led to unstable models or individual CL prediction bias. Three explanations for the observed discrepancies, (i) non-considered maturation of processes such as absorption or first-pass effect, (ii) lack of patients between 1 and 12 months, (iii) lack of correction of PBPK CL-maturation functions derived from urinary concentration ratio data for the renal function relative to adults. should be investigated in the future to determine how NLME and PBPK methods can work towards deriving insights into pediatric hydrocortisone PK.